When People Speak (Novel Prolom by Branko Copić) - Kostić, Dragomir J. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The epic novel by Branko Ćopić, Prolom, talks about the resistance of the people of Podgorina (of Bosanska Krajina), the pogrom violence of Ustaša and NDH (Independent State of Croatia), and the confusion and dissension among people on how to respond to this great evil that has happened to them. The novel was surpressed, maybe even forgotten, for two reasons. Firstly, beacuse of its scope of threatening verbosity, although the novel reads quite easily, like an exciting adventure. Secondly, the writer’s ideas of brotherhood among all peoplewas brutally trampled in the nineties of last century in whole Yugoslavia, and particularly in Bosnia and Herzegovina. This novel provides a comprehensive picture of the national life in the neighborhood of evil and death. Therefore, this novel represent a ferocious roar of the people against evil and repression and as such it cannot be hurt by time. It has become the part of its people; spoken in their own language and integral to their historical and civilizational being.